2017
DOI: 10.1002/adv.21926
|View full text |Cite
|
Sign up to set email alerts
|

Improved interfacial properties of carbon fiber composites by building stress transition layer with carbon nanotubes

Abstract: For the purpose of improvement in interfacial property of carbon fiber composites through a facile process, the carboxyl-functionalized multiwalled carbon nanotubes (MWCNTs-COOH) were incorporated into the surface of JH-T800 carbon fiber using sizing and deposition technology. The surface morphology of MWCNTs-COOH-modified carbon fibers and fracture surfaces of unidirectional carbon fiber composites were observed via scanning electron microscopy and atomic force microscopy. According to the results of composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…The study of Xiao et al [ 112 ] and Zhang et al [ 113 ] suggested that, among the existing method for grafting CF with CNT, aqueous suspension deposition is the most facile and finds better reinforcing efficacy than others due to its feasibility for large-scale production. In addition to a better throughput rate, this method rules out any complex chemical and equipment prerequisite and assures impeccable fiber surface, which prompts better interfacial property.…”
Section: Mechanical Performance Of Different Carbonaceous Compositementioning
confidence: 99%
See 1 more Smart Citation
“…The study of Xiao et al [ 112 ] and Zhang et al [ 113 ] suggested that, among the existing method for grafting CF with CNT, aqueous suspension deposition is the most facile and finds better reinforcing efficacy than others due to its feasibility for large-scale production. In addition to a better throughput rate, this method rules out any complex chemical and equipment prerequisite and assures impeccable fiber surface, which prompts better interfacial property.…”
Section: Mechanical Performance Of Different Carbonaceous Compositementioning
confidence: 99%
“…Higher interfacial property can also be achieved by functionalization of the carboxyl group in CNT [ 116 ]. Zhang et al [ 113 ] coated carboxyl-functionalized MWCNT on CF, employing both sizing and deposition methods together. The result was startling as a 32.06% increase of IFSS was observed in hierarchical composite compared to raw CFRP, which has its origin in two separate distribution states of MWCNT, triggering a reinforcement layer having gradient discrepancy of modulus, which paves the way for boosted load transfer.…”
Section: Mechanical Performance Of Different Carbonaceous Compositementioning
confidence: 99%
“…However, electrical and thermal conductivities are not strong suits of the CF fabrics, limiting their functional applications. Also, due to their high stiffness, weaving CFs is difficult and forming strong interactions between fibers is even more challenging. , Compared to bonding in CFs, direct interfiber bonding between GFs can be established by the wet-fusing assembly, forming the basis for fabricating electrically and thermally conductive nonwoven GF fabrics …”
Section: Unique Microstructure Control Methods For Graphene Papers An...mentioning
confidence: 99%
“…Also, due to their high stiffness, weaving CFs is difficult and forming strong interactions between fibers is even more challenging. 56,57 Compared to bonding in CFs, direct interfiber bonding between GFs can be established by the wet-fusing assembly, forming the basis for fabricating electrically and thermally conductive nonwoven GF fabrics. 58 When redispersed into an aqueous solvent, dried GOFs are immediately wetted.…”
Section: Wet-fusing Technique For Forming Flexible Yet Conductive Gfmsmentioning
confidence: 99%